Penguatan Kelembagaan Karang Taruna Melalui Ruang Perjumpaan Dusun Pir 25 Desa Pagar Jati Kecamatan Semidang Lagan Kabupaten Bengkulu Tengah - Syarifin, Ahmad; Deka, Agustin Tiara; Juniarti, Yulia; Al Mustofa, Iim Ibrohim (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
This service intends to see the benefits of meeting space in strengthening the Youth Organization in Pir 25 Hamlet, Pagar Jati Village. The focus of this activity is on Strengthening the Youth Organization through Meeting Room. This service aims to provide a forum for discussion for the Youth Organization of Pir 25 Hamlet regarding the importance of Youth Organization and Youth Organization plans for the future. The target of this activity is the youth organization Karang Taruna Dusun Pir 25 Pagar Jati Village, totaling 33 people. The method used is the focus group discussion method. In this focus group discussion, the process of activities carried out is to increase understanding of the importance of Youth Organization, re-establish the organizational structure of Youth Organization, increase understanding of the responsibilities and duties of each division, and formulate Youth Organization work programs. The results of this activity are that Karang Taruna Pir 25's understanding of the importance of Youth Organization has increased, where Karang Taruna Pir 25 knows the role, benefits and goals of an active Youth Organization for the community environment, the organizational structure of Karang Taruna Pir 25 is re-established in a more structured manner, Karang Taruna Pir 25's understanding of the obligations of each division has increased, Karang Taruna Pir 25 already has a work program plan and knows how to develop a work program plan. There are work programs that they have carried out, namely community meetings and independence day commemorations.